Normal extensions of a singular differential operator on the right semi-axis - Ismailov, Zameddin I.; Öztürk Mert, Rukiye (Eurasian Mathematical Journal, 2014)
In this work, based on the method of Everitt-Zettl and using the Calkin-Gorbachuk method, all normal extensions of the minimal operator generated by a linear singular formally normal differential-operator expression of the first order in Hilbert spaces of vector-functions on the right semi-axis in terms of boundary values are described. Furthermore, the structure of the spectrum of these extensions is investigated.